2009
DOI: 10.1590/s0102-695x2009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic and hipotensive activity of aqueous extract of parsley seeds (Petroselinum sativum Hoffm.) in rats

Abstract: RESUMO: "Atividade diurética e hipotensora do extrato aquoso da semente de salsa (Petroselinum sativum Hoffm.) em ratos". A espécie vegetal, Petroselinum sativum Hoff, conhecida como salsa, é amplamente utilizada na medicina popular brasileira como diurético. O objetivo desse estudo é verificar se o uso brasileiro do extrato aquoso da salsa tem efeitos semelhantes com investigações que mostram o efeito diurético da P. sativum em ratos. Métodos: 19 ratos foram anestesiados e canulamos a traquéia, artéria caróti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
12
0
5
Order By: Relevance
“…In our study, B. holophylla treatment did not interfere in blood glucose levels of the diabetic and it causes no hypoglycemia in non-diabetic rats. This might be justified due to administered dose, extraction method, short treatment period, and the sensitivity difference among the plants used and the animals tested (Campos et al 2009), which would prevent the effective action by the plant extract. Another variable to consider is the type of diabetes studied.…”
Section: Bauhinia Holophylla In Diabetic Rats 269mentioning
confidence: 99%
“…In our study, B. holophylla treatment did not interfere in blood glucose levels of the diabetic and it causes no hypoglycemia in non-diabetic rats. This might be justified due to administered dose, extraction method, short treatment period, and the sensitivity difference among the plants used and the animals tested (Campos et al 2009), which would prevent the effective action by the plant extract. Another variable to consider is the type of diabetes studied.…”
Section: Bauhinia Holophylla In Diabetic Rats 269mentioning
confidence: 99%
“…One of the widely used vegetal species in various nations' medicine is parsley (Petroselinum crispum), which has remedial effects as a powerful diuretic agent [1,2], an abortifacient [3][4][5] and an expectorant [6,7]. Parsley is a native herb of the central Mediterranean region (southern Italy, Algeria and Tunisia), which is in the Apiaceae family, and is a species of Petroselinum [8].…”
Section: Parsley and Immunomodulationmentioning
confidence: 99%
“…Matching the wide use of this vegetal species as a diuretic in folk medicine, natriuretic and hypotensive effects of parsley were demonstrated in studies by Kreydiyyeh and Usta, and de Campos et al [1,2]. Further studies indicated more biological effects of parsley plants, such as provitamine A activity, and influencing the cell signaling pathways [22,23].…”
Section: Parsley and Immunomodulationmentioning
confidence: 99%
“…Além disso, o Brasil possui mais de 20% da parcela total da biodiversidade mundial e uma grande diversidade étnica e cultural, caracterizando-o como detentor do potencial necessário para o desenvolvimento de pesquisas com resultados tecnológicos e terapêuticos (BRASIL, 2006;FIRMO et al, 2011;SALES et al, 2015;BRASIL, 2018). Neste sentido, com o objetivo de preservar e estudar mais detalhadamente a flora local, em 1996 foi implantado, em uma área de 30.000m², o projeto do Horto Medicinal do Campus 2 da Universidade Paranaense, localizado em Umuarama -PR (CANZI et al, 2012). Os mesmos autores, Canzi et al (2012) enfatizam para a flora do Horto Medicinal a ocorrência de 333 espécies pertencentes a 257 gêneros e 89 famílias, mostrando uma variedade significativa com o desenvolvimento de inúmeros trabalhos científicos.…”
Section: Introductionunclassified